Secularization: A Response from Canon Law Based on the Concept of the “Church on the Move” and Cooperation with the Civil Order in Cases of Abuse of Minors by Priests - Salinas Mengual, Jorge (Religions, 2024)
The influence of secularization and secularism in today’s society has led to a process of privatization of religion. Faced with this reality, Pope Francis, in his Apostolic Exhortation Evangelii gaudium, has promoted the need for a pastoral conversion, betting on a “Church going out” that, on the one hand, can cope with this process and, on the other hand, go out to meet all those people who suffer in the existential peripheries. The aim of this paper is to demonstrate, through a qualitative and quantitative methodology, how canon law is a reality that cannot stand aside from this call and how, in the specific area of child abuse within the Church, it must opt for a position that we call “expansion” or extra ecclesiam, capable of recognizing and dealing with the cases that have occurred, as well as operating a system of cooperation with the civil order, with the aim of promoting justice and the common good of society, in order to limit the growing process of secularization.
Keywords: secularization; departing church; canon law; sexual abuse of minors; cooperation